Potential of International Project Activity for University Development - E. V. Kudryashova; L. A. Zarubina; S. V. Popkova; N. V. Baykina (Высшее образование в России, 2020)
In the context of global competition, Russian universities search for the most efficient solutions to achieve competitiveness in the global market. The particular challenges that Russian universities face today include enhancing the quality of education and research, development of export potential, integration into international academic environment, diversification and search for new financial sources. The article considers international project activity as the most efficient tool of university internationalization process and solving the university tasks. Fundraising and international projects provide substantial support for achieving the set objectives in terms of both allocating additional financial resources and attracting intellectual capacity of international partners. Due to such features as practice orientation, time limits, and the ability to integrate different types and forms of international cooperation, the projects help university to address the challenges in a complex way and achieve multiple effects and, therefore, contribute significantly to developing world-demanded research, creating scholars networks and publishing, strengthening international partnerships, capacity building, enhancing academic mobility, developing the university campus and its infrastructure. The authors present the management model of international fundraising and projects implementation at Northern (Arctic) Federal University named after M. Lomonosov, describe specific features of carrying out research and educational projects in cross-cultural context (also within the framework of cross-border cooperation in Barents Euro-Arctic Region). The article outlines the competences required for successful project implementation, gives examples of NArFU international projects aimed at solving challenges in the Arctic Region. The efficiency of the given management model is analyzed, also by presenting the results of sociological survey made with involvement of the projects participants.